Effects of the angle of attack on the aerodynamic characteristics of a streamlined box girder. Issue 10 (July 2021) - Li, Hao-Hong; Zhang, Liang-Liang; Wu, Bo; Ni, Zhi-Jun; Yang, Yang
This paper presents experimental and numerical approaches to systematically investigate the aerodynamic characteristics of streamlined box girder at angles of attack (AoA) of up to 12°. The effects of AoA on the pressure characteristics and total forces are first studied through wind tunnel experiments. Based on three-dimensional large-eddy simulations (3D LES), the flow topology is investigated to study the influence mechanism of AoAs. The results show that the flow topology around the section can be divided into three types: (i) completely attached flow pattern as |α| ≤ 4°; (ii) separated-reattached flow pattern as 6°≤|α|≤8°; (iii) fully separated flow pattern as |α| ≥ 10°. The combination of experimental and numerical results presents a deep understanding of the aerodynamic characteristics of a streamlined box girder and reveals the relationships between the pressure features and flow topology. The pressure characteristics and total forces are very sensitive to the flow separation and reattachment. At small AoAs, the flow attaches to the bridge section, the mean and RMS pressure, total force, as well as streamwise correlations change slightly with AoAs. Besides, the shear layer is a laminar pattern and has less impact on the span-wise correlations. Moreover, the vortices in the wake remain successive in the span-wise direction, and the Strouhal numbers are larger. On the other hand, with the increase of AoAs, large separation bubbles can be observed around the bridge section. Especially for fully separated flow pattern as |α| ≥ 10°, the shear layer no longer attaches to the bridge section and the separation bubble is longer than the section width. Accordingly, the mean and RMS pressure, total force, as well as streamwise correlations increase significantly. Besides, the shear layer is a turbulent pattern, and the turbulent fluctuations in wake become complex and less organized in the span-wise direction, then the St is lower than others.